The relationship of physical performance with HIV disease and mortality - Greene, Meredith (AIDS, 2014)
OBJECTIVE: To evaluate whether HIV infection was associated with reduced physical performance, and to examine if reduced physical performance predicted mortality in our aging cohort of HIV-infected and HIV-uninfected persons. DESIGN: Prospective, observational cohort of current and former injection drug users in the AIDS Linked to the IntraVenous Experience study in Baltimore, Maryland, USA. METHODS: The Short Physical Performance Battery (SPPB) was used as an objective measure of physical performance and measured semiannually along with behavioral and demographic data. Correlates of reduced physical performance (SPPB score ≤10) were identified and the relationship between reduced physical performance, HIV infection and mortality was analyzed by Cox regression. RESULTS: Among 12 270 person-visits contributed by 1627 participants, the median age was 51, 30.3% were HIV-infected and 32.6% had an SPPB score 10 or less. In multivariable models, HIV infection was independently associated with 30% increased odds of reduced physical performance [odds ratio 1.30; 95% confidence interval (CI):1.12–1.52]. Reduced physical performance predicted mortality in a dose-response manner and within all HIV disease strata. Whereas reduced physical performance alone (hazard ratio 2.52, 95% CI: 1.59–4.00) and HIV infection alone (hazard ratio 2.78, 95% CI: 1.70–4.54) increased mortality, HIV-infected participants with reduced physical performance had a six-fold increased mortality risk (hazard ratio 6.03, 95% CI: 3.80–10.0) compared with HIV-uninfected participants with higher physical performance. CONCLUSION: HIV infection was independently associated with reduced physical performance. HIV and reduced physical performance have independent and joint effects on mortality. Physical performance measurement may be an important research and clinical tool to predict adverse outcomes among aging HIV-infected persons.